Dose verification procedures in radiotherapy - Zakaria, Ahmad; Idris, Nik Rusman Nik (1999)
In radiotheraphy the accuracy of the radiation dose to be delivered to patient is vital.In the current practice the dose to be delivered by the treatment machine is calculated using computer planning system which utilised computational algorithms based on mathematical model that takes into account the shape of treatment beam, target geometry and tissue inhomogeneities present in the patient. To ensure the safe and accurate delivery of the prescribed dose the dose distributions predicted by the system must be validated before use in clinical setting. The aim of this work was to establish simple and practical test cases that would permit comparison of computed doses with measured values in order to verify the accuracy of the dose computation process in our treatment planning system. In our study the dose at selected points for each test condition consisting of beam-phantom configuration irradiated with 6MV photon beam wascomputed with Nucletron PLATO RTS treatment planning computer using pencil beam algorithms. The computer predicted values were compared with dose values obtained from measurements. Based on 6 MV input beam data, geometry of the phantom and the chosen treatment set up, the computer generated the isodose curves for each test condition. The dose was then prescribed at a chosen isodose line. The computer then calculated the treatment monitor units for the machine and also the absolute dose at any selected point in the phantom for each test condition.Using the same monitor unit calculated and the same test condition the photon beam was then applied to the phantom and the absolute dose at selected points was determined by measurement based on the charges collected by ionization chamber. The charges collected at the selected points were converted to absolute dose using American Association of Physicists in Medicine Task Group 21 (AAPM TG 21) Protocol.The test cases carried out in this study include open square field and normal incidence, rectangular field, wedged, oblique incidence and non-flat surface, open square field with lung and bone inhomogeneities. In most test cases dose variations were less than 2%. The variation between measured and calculated data for all the test conditions ranged from 0.3% to 6.9%. Our results showed that the algorithms (pencil beam) in the planning computer gave acceptable accuracy for our test cases. The test conditions that we have established are simple to carry out and well-suited as part of QA procedures for treatment planning system before use in clinical setting.